Gene expression in the brain of a migratory songbird during breeding and migration. Issue 1 (December 2016) - Boss, John; Liedvogel, Miriam; Lundberg, Max; Olsson, Peter; Reischke, Nils; Naurin, Sara; Åkesson, Susanne; Hasselquist, Dennis; Wright, Anthony; Grahn, Mats; Bensch, Staffan
Abstract Background We still have limited knowledge about the underlying genetic mechanisms that enable migrating species of birds to navigate the globe. Here we make an attempt to get insight into the genetic architecture controlling this complex innate behaviour. We contrast the gene expression profiles of two closely related songbird subspecies with divergent migratory phenotypes. In addition to comparing differences in migratory strategy we include a temporal component and contrast patterns between breeding adults and autumn migrating juvenile birds of both subspecies. The two willow warbler subspecies, Phylloscopus trochilus trochilus andP. t. acredula, are remarkably similar both in phenotype and genotype and have a narrow contact zone in central Scandinavia. Here we used a microarray gene chip representing 23, 136 expressed sequence tags (ESTs) from the zebra finchTaeniopygia guttata to identify mRNA level differences in willow warbler brain tissue in relation to subspecies and season. Results Out of the 22, 109 EST probe sets that remained after filtering poorly binding probes, we found 11, 898 (51.8 %) probe sets that could be reliably and uniquely matched to a total of 6, 758 orthologous zebra finch genes. The two subspecies showed very similar levels of gene expression with less than 0.1 % of the probe sets being significantly differentially expressed. In contrast, 3, 045 (13.8 %) probe sets were found to be differently regulated between samples collected from breeding adults and autumn migrating juvenile birds. The genes found to be differentially expressed between seasons appeared to be enriched for functional roles in neuronal firing and neuronal synapse formation. Conclusions Our results show that only few genes are differentially expressed between the subspecies. This suggests that the different migration strategies of the subspecies might be governed by few genes, or that the expression patterns of those genes are time-structured or tissue-specific in ways, which our approach fails to uncover. Our findings will be useful in the planning of new experiments designed to unravel the genes involved in the migratory program of birds.